The reality of food losses: a new measurement methodology - Delgado, Luciana; Schuster, Monica; Torero, Máximo (Instituto Nacional de Innovación Agraria, 2018)
Measuring food loss, identifying where in the food system it occurs, and developing effective policies along the value chain are essential first steps toward addressing the problem in developing countries